Ottomanism and Neo-Ottomanism in the Travails of the ‘Serbian National Corpus’: Turkey as the Recurrent Focus of Serbian Academia - Dević, Ana (Die Welt des Islams, 2016)
This study addresses the revival of ‘Ottomanism’, defined as a threat of ‘return’ to the cultural and political norms of the Ottoman Empire, operationalized via the links between Turkey and the local Muslim population, among the academic elites in Serbia since the late 1980s. The making of Ottomanism a relevant segment of the nation-building process in post-Yugoslav Serbia has served two goals: (1) forgetting the history of the Yugoslav Federation; and (2) affirming the ‘irreconcilable differences’ between the Yugoslav Muslims and Christians, and subsequently legitimating the violent redrawing of state boundaries. The neo-Ottomanist ‘dangers’ are presented as stemming from: (1) the apparent continuity between the expansionism of the Ottoman Empire and the current policies of Turkey in the Balkans, (2) the failure of the modernization reforms of ‘Atatürkism’, which is attributed to the fact that they were alien to the cultural-religious ‘essence’ of Turkish mentality; and (3) the link between the modernization failure and the resurgence of ‘Islamization’, which is perceived as either not been recognized by Turkey’s Western allies, or as being used by U.S. policymakers as leverage against other Middle Eastern states.